Promoting Better Dispute Decision-Making with an AI Tool Built on RPS Theory - John Lande (Washington University Journal of Law and Policy, 2026)
Traditional theories of negotiation and mediation rely on rigid models, false dichotomies, and confusing terminology that fail to reflect the complexity of real practice. This Article critiques those theories and introduces Real Practice Systems theory as a more accurate and practical alternative. RPS Theory conceptualizes negotiation and mediation as sequences of professional judgment shaped by context, experience, and goals rather than as idealized or linear processes. It promotes a realistic and ethically responsible practice by encouraging reflection, intentional process design, and adaptability. The Article introduces RPS Coach, a free artificial intelligence tool built on ChatGPT. It is designed to promote good decision-making by parties, lawyers, mediators, educators, and program administrators. It helps users prepare, analyze, reflect, and improve their practice habits over time. The Article concludes by considering the promise and limitations of AI in dispute resolution and offers a vision for AI tools that enhance rather than replace human judgment.
Keywords: #RealPracticeSystems; #RPSTheory; #AIDisputeResolution; #MediationPractice; #LegalAIethics; #AdaptiveMediation